Specificity of Treatment for Prosthetics of Large Joints in HIVInfected Patients - Gaffarov X.A; M. E. Pulotov (Genius Journals, 2023)
There are a limited number of publications that present the results of primary end prosthetics of large joints in patients with human immunodeficiency virus (HIV). We could not find any works devoted to revision end prosthetics in patients with periprosthetic infection. During the period from 2015 to 2019, 13 HIV-positive patients with periprosthetic infection of the hip (10 cases) and knee (3 cases) joints were treated at the clinic. The patients' condition was assessed using clinical, laboratory, and radiological methods. The Harris Hip Score and Knee Society Score were evaluated before and after surgery. Despite compliance with international protocols for the treatment of implant-associated infection, the frequency of relapses in HIV-positive patients in the asymptomatic stage remains very high. The effectiveness of two-stage treatment using an antibacterial spacer in our group of patients was only 15.4%.
Keywords: Periprosthetic infection; revision end prosthetics; HIV infection